PTU-072 A multi-centre review of acute upper GI bleeding; can blood urea levels aid diagnosis?. (June 2019) - Kotecha, Deevia; Mak, Jason; Sharma, Neel; Boulton, Ralph; Disney, Benjamin; Bhala, Neeraj; Verma, Ajay
Abstract : Introduction: Risk scoring for acute upper gastrointestinal bleeding (AUGIB) is key when assessing patients for requiring OGD. The Rockall score utilises age, comorbidities and shock. The Glasgow-Blatchford score (GBS), in addition, utilises haemoglobin, melaena, and blood urea levels. Raised blood urea levels can represent digestion of blood from the upper gastrointestinal tract giving rise to melaena; the presence of both gives a high GBS. However, inexperienced health care professionals can misinterpret the absence/presence of melaena, raised urea levels may be due to kidney injury. Nevertheless, Gastroenterologists may use urea to diagnose AUGIB if patients haven't had overt/witnessed/reliably reported haematemesis or melaena. It has been shown that a raised urea:creatinine ratio (URCR) can be associated with AUGIB and may be superior to urea alone as it mitigates for kidney injury. 1 However, URCR is not widely used in the UK in the assessment of AUGIB. We aim to assess the association of urea and URCR levels with AUGIB. Methods: A retrospective review at three UK centres (Kettering General Hospital, Queen Elizabeth Hospital Birmingham, and University Hospital Coventry & Warwickshire) was undertaken. Endoscopy reports and blood tests were reviewed of patients undergoing inpatient OGD for suspected AUGIB within 2017/8, data were recorded in an Excel spreadsheet. URCR was calculated by dividing Urea by creatinine, and multiplying by 1000 (abnormal = ≥100). Statistics were analysed using SPSS. Results: 357 patients' records were reviewed (median age = 68), 179 had a plausible AUGIB (50.1%). Receiver operator characteristic (ROC) curves for Urea gave an area under the curve (AUC) = 0.733 . For URCR, AUC = 0.789 . Binary logistic regression modelling was performed using age, urea, and URCR. χ 2 (3, n = 357) = 102.92, p<0.001. 25–34% of the variance in AUGIB is explained by the model. The model URCR value of 97.7 can be used to predict AUGIB, applying this to our data set correctly identifies 124/179 patients with AUGIB (69.3%), and is predicted to correctly identify 74.5 % . Conclusion: This pilot study has limitations as bleeding lesions may have not been identified at OGD. Urea and URCR have AUCs of 0.733, & 0.789. Logistic regression modelling suggests a URCR level of 100 would correctly identify ∼70% of AUGIB in patients with suggestive symptoms. Outside of firm indications for OGD in suspected AUGIB (shock, previous/suspected variceal bleed), a raised URCR appears to be a useful marker to predict AUGIB: a larger study would be able to test this robustly. Reference: Srygley FD, Gerardo CI, Tran T, Fisher DA. Does this patient have a severe upper gastrointestinal bleed? JAMA 2012;307(10):1072–9.